Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Antimicrobial photodynamic therapy encapsulation technology: Frontier exploration and application prospects of novel antimicrobial technology - Xianjin Hu; Bingbing Shou; Lu Yang; Letian Li; Hai-Tao Ren; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Chitosan-based antibacterial microspheres loaded multifunctional Janus composite membranes with unidirectional biofluid transport, antioxidant and pH-responsive monitoring - Ting-Ting Li; Li Sun; Ying Zhang; Bing-Chiuan Shiu; Hai-Tao Ren; Hao-Kai Peng; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Preparation and study of bark-like MXene based high output power hydroelectric generator - Xiaoyang Zhang; Yanting Wang; Xuefei Zhang; Ching-Wen Lou; Jia-Horng Lin; Ting-Ting Li (Chemical Engineering Journal, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Modelling chloroform in indoor swimming pool air and water: the influences of internal air circulation and occupants - Hui-Tsung Hsu; Ming-Jen Chen; Kuang-Chung Tsai; Li-Jen Huang; Ching-Ho Lin; Chin-Hsing Lai; Li-Hsin Cheng (Environmental Science and Pollution Research, 2023)

Health Risk of Infants Exposed to Lead and Mercury Through Breastfeeding - Yung-Chieh Lin; Wei-Hsiang Chang; Tsun-Ching Li; Osuke Iwata; Hsiu-Ling Chen (Exposure and Health, 2023)
Donor milk from the human milk bank is important for vulnerable infants without their mothers’ own milk. Longitudinal changes in toxic metals in donor milk has not been reported. This study aimed to assess the effect of donors’ demographic characteristics, life habits and dietary habits on the concentration of metals in breastmilk donated to a human milk bank and to assess the health risk of lead (Pb) and mercury (Hg) exposure of donor mothers’ offspring through breastfeeding and the vulnerable recipients. A total of 228 samples, which were longitudinally donated to the human milk bank by 39 donors, were selected specifically to assess the levels of Pb, Hg, and MeHg. Donors’ offspring were also enrolled as mother-infant-dyads to monthly obtain the milk consumption and body weight. The results showed significant differences in the infant risk in exclusive breastfeeding months. The average Pb level of breast milk was 6.49 ± 5.23 µg/L (mean ± standard deviation), and the Hg level was 0.76 ± 0.98 µg/L. The sources of these toxins—residential districts, cleaning products, cosmetics, drinking water, viscera, eggs, seafood, and canned food—have a significant influence on the concentration of toxic metals in human milk. This study showed an unacceptable non-cancerous health risk (95th percentile hazard index, HI = 1.37 > 1) for Pb and Hg. In the future, the breast milk offered by the bank should be strictly monitored, especial for Pb, to ensure high-quality donor milk for vulnerable recipients but also donor mothers’ offspring who depend on it. Graphical Abstract

Enhancing mechanical and photocatalytic properties by surface microstructure regulation of TiO2 nanofiber membranes - Xilin Liao; Hai-Tao Ren; Baolei Shen; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemosphere, 2023)

Sputter-deposited nickel nanoparticles on Kevlar fabrics with laser-induced graphene for efficient solar evaporation - Shuaihang Zhu; Zhiwei Lei; Yuejie Dou; Ching-Wen Lou; Jia-Horng Lin; Jiwei Li (Chemical Engineering Journal, 2023)